Persistent atrial fibrillation: A systematic review and meta-analysis of invasive strategies. (1st March 2019) - Berger, Wouter R.; Meulendijks, Eva R.; Limpens, Jacqueline; van den Berg, Nicoline W.E.; Neefs, Jolien; Driessen, Antoine H.G.; Krul, Sébastien P.J.; van Boven, Wim Jan P.; de Groot, Joris R.
Abstract: Background: Persistent atrial fibrillation (AF) is associated with higher stroke and mortality risk than paroxysmal AF (pAF). Outcomes of catheter or surgical ablation are worse in patients with persistent AF than in pAF, and the optimal invasive rhythm control strategy has not been established. Purpose: We provide a contemporary systematic overview on efficacy and safety of catheter and minimally-invasive surgical ablation for persistent AF. Methods: We systematically searched EMBASE, MEDLINE and CENTRAL from inception to July 2018 for randomized trials on surgical and catheter ablation, and included all study arms on persistent AF. Outcome was AF freedom after ≥12 months follow-up without AAD use. Random effects models were used to calculate proportions with 95%-confidence intervals. Safety consisted of adverse events during treatment and follow-up. Results: We included 6 studies on minimally-invasive surgical ablation and 56 on catheter ablation, involving 7624 patients with persistent AF. AF Freedom at 12 months was 69% (95%CI 64–74%) after surgical and 51% (95%CI 46–56%) after catheter ablation. More severe procedural adverse events occurred with surgery than with catheter ablation. Conclusions: In persistent AF patients, minimally-invasive surgical ablation is associated with more procedural complications, but higher AF freedom. As adverse events after surgical ablation appear more severe than in catheter ablation, a patient-tailored therapy choice is warranted. Highlights: Freedom of atrial fibrillation recurrence was higher after minimally-invasive surgical ablation compared to catheter ablation in persistent AF More severe procedural adverse events occurred with surgical ablation than with catheter ablation. A patient-tailored therapy choice in patients with persistent atrial fibrillation is warranted.